The income elasticity of participation in physical activity: evidence from Malaysia - Yong, Kang Cheah; Omar, Mohd Azahadi; Siew, Nooi Phang; Abd. Manaf, Noor Hazilah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Estimating the income elasticity of demand for market goods and services has received significant research attention. However, the income elasticity of participation in physical activity has never been studied thoroughly, especially in developing countries. To fill this research gap, the income elasticity of time spent in both vigorous and moderate physical activities is estimated using a two-part model. Data from the National Health and Morbidity Survey 2011 is used. After controlling for demographic variables, the present study finds that time spent in vigorous and moderate physical activities is negatively associated with income. However, the degree of sensitivity of time spent in vigorous and moderate physical activities is low, suggesting that income does not play an important role in promoting physically active lifestyle among adults. The present study concludes that acquiring a better understanding of the income elasticity of physical activity is important for policy development.